Karakteristik Sifat Kimia Tanah Pada Tegakan Tanaman Kelapa Sawit (Studi Kasus di Kebun Milik Rakyat di Desa Perlabian Kecamatan Kampung Rakyat Kabupaten Labuhanbatu Selatan) - Muhammad Fahrur Rozi Harahap; Hilwa Walida; Yudi Triyanto (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2023)
Soil chemical properties have an important role in the growth and production of oil palm. Plants need nutrients to increase productivity. Oil palm (Elaeisguineensis Jacq) is the main plantation crop in Indonesia. This study aims to determine the characteristics of soil chemical properties in oil palm plantation stands of the people of Perlabian Village, South Labuhanbatu District, Kampung Rakyat District. The method used is a free grid survey method at the semi-detail survey level. Oil palm soil samples were taken from 6 oil palm sample trees with an area of 1 hectare. The parameters of the chemical properties of the soil are the content of N, P, K, Mg, pH, C-organic, and C/N. Data analysis was done by descriptive method. The results showed that the chemical properties of the soil in the people's garden of Perlabian Village, South Labuhanbatu Village, showed that the N-soil content was 0.14% (low), P-soil was 140.60 ppm (very high), K-soil was 0.08 me /100g (very low), Mg 0.09 me/100g (very low), pH level 5.00 (sour), C-organic content 3.48% (high), and C/N ratio 24.86 (high). Therefore, the chemical properties of the soil in the people's garden of Perlabian Village, South Labuhanbatu Village, still require proper fertilization to meet the needs of macro and micro nutrients in the soil.Keywords: Oil Palm, Chemical Properties, SoilKarakteristik Sifat Kimia Tanah Pada Tegakan Tanaman Kelapa Sawit (Studi Kasus di Kebun Milik Rakyat di Desa Perlabian Kecamatan Kampung Rakyat Kabupaten Labuhanbatu Selatan)